A NEW SPECIES OF MACHAERODONT FROM MAKAPANSGAT - Collings, G. E. (BERNARD PRICE INSTITUTE FOR PALAEONTOLOGICAL RESEARCH, 1972)
The skull and associated mandible belonging to a new species of machaerodont, Megantereon problematicus Collings is described. The specimen came from the lowermost horizon of banded and contaminated travertines at the Makapansgat Limeworks. An estimate of its relationship with other sabre tooth cats is given.